Analisis Determinan Kualitas Produk dan Desain Produk Terhadap Keputusan Pembelian Pada CV Legenda Timur Indonesia - Nurvi Oktiani; Rizaldi Barez (CV. Ulil Albab Corp, 2024)
Currently the apparel industry is the industrial sector that is most popular with all consumers, so various efforts are made by companies to increase purchases made by consumers, several ways are carried out by producers or companies by improving product quality and product design, the aim of the research is to determine variables, namely product quality and product design that can determine and differentiate purchasing decisions. Research was carried out with a quantitative research design, with data collection methods through distributing questionnaires with 100 respondents, data processing was carried out using Determinant Analysis with Steps between Determining Averages the average discriminant variable between groups, the stage of determining the discriminant function, determining the estimated discriminant function, so that the research results show that the Canonical Correlation value is 0.890 or the canonical correlation (CR2): or the same as 0.7921, so it can be concluded that 79.21% of the variation in decisions Purchasing can be explained through product design and product quality. From the standard Canonical Discriminant Function Coefficient table, the Product Design discriminant variable (0.684) is relatively more important in forming the discriminant function in improving consumer purchasing decisions compared to product quality.